Asian development review. - Sawada, Yasuyuki (Asian development review, 2020)
This issue includes a guide to the ADB COVID-19 Policy Database and articles on trade, manufacturing, human capital, and education in Asia and the Pacific. It covers topics that include reducing arsenic poisoning, borrowing versus saving among migrant workers, the role of knowledge transfers in promoting balanced growth, and trade volatility. It covers topics that include reducing arsenic poisoning, borrowing versus saving among migrant workers, the role of knowledge transfers in promoting balanced growth, and trade volatility.